2019
DOI: 10.1111/cas.13906
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the mutational landscape and fragmentation of circulating tumor DNA in renal cell carcinoma

Abstract: Reliable biomarkers for renal cell carcinoma (RCC) have yet to be determined. Circulating tumor DNA (ctDNA) is an emerging resource to detect and monitor molecular characteristics of various tumors. The present study aims to clarify the clinical utility of ctDNA for RCC. Fifty‐three patients histologically diagnosed with clear cell RCC were enrolled. Targeted sequencing was carried out using plasma cell‐free DNA (cfDNA) and tumor DNA. We applied droplet digital PCR (ddPCR) to validate detected mutations. cfDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 42 publications
6
71
0
3
Order By: Relevance
“…In our cohort, only surgical specimens were used to define WHO/ISUP grade because the diagnostic accuracy of tumour grade between biopsy and surgical pathology was reported to be around 50-75% 32,33 . Recently, the importance and versatility of biopsy of the renal mass or metastatic lesions have rapidly increased, and the development of a means of accurate diagnosis using liquid biopsy is needed 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, only surgical specimens were used to define WHO/ISUP grade because the diagnostic accuracy of tumour grade between biopsy and surgical pathology was reported to be around 50-75% 32,33 . Recently, the importance and versatility of biopsy of the renal mass or metastatic lesions have rapidly increased, and the development of a means of accurate diagnosis using liquid biopsy is needed 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies suggested low detection rates and/or levels of ctDNA in locally advanced and metastatic RCC [6,9,10] . More recently targeted sequencing detected ctDNA in 30% of 53 RCC patients [11] . Conversely, Pal and colleagues (2017a) detected ctDNA in 78.6% of 200 metastatic patients using the Guardant360 plasma assay (Guardant Health), though with a median of one genomic alteration per sample [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite showing great promise in various cancers [6] , there is little and often contradictory data of ctDNA as a tool in RCC in locally advanced and metastatic RCC [6,[9][10][11] . As such, there remains an unmet need for the characterisation of the levels, and potential clinical utility, of ctDNA in renal cancers of differing stage and subtype.…”
Section: Introductionmentioning
confidence: 99%
“…In einigen wenigen Publikationen konnte so ctDNA nachgewiesen werden, wie z. B. für metastasierte Patienten unter TKI-Therapie [51,52]. Voraussetzung für eine kli-nische Umsetzung ist jedoch die Kenntnis der häufigsten Mutationen.…”
Section: Liquid Biopsiesunclassified